Genetic risk factors for VIPN in childhood acute lymphoblastic leukemia patients identified using whole-exome sequencing. (7th September 2018) - Abaji, Rachid; Ceppi, Francesco; Patel, Swati; Gagné, Vincent; Xu, Chang J; Spinella, Jean-François; Colombini, Antonella; Parasole, Rosanna; Buldini, Barbara; Basso, Giuseppe; Conter, Valentino; Cazzaniga, Giovanni; et al.
Aim: To identify genetic markers associated with vincristine-induced peripheral neuropathy (VIPN) in childhood acute lymphoblastic leukemia.Patients & methods: Whole-exome sequencing data were combined with exome-wide association study to identify predicted-functional germline variants associated with high-grade VIPN. Genotyping was then performed for top-ranked signals (n = 237), followed by validation in independent replication group (n = 405).Results: Minor alleles of rs2781377/ SYNE2 (p = 0.01) and rs10513762/ MRPL47 (p = 0.01) showed increased risk, whereas that of rs3803357/ BAHD1 had a protective effect (p = 0.007). Using a genetic model based on weighted genetic risk scores, an additive effect of combining these loci was observed (p = 0.003). The addition of rs1135989/ ACTG1 further enhanced model performance (p = 0.0001).Conclusion: Variants in SYNE2, MRPL47 and BAHD1 genes are putative new risk factors for VIPN in childhood acute lymphoblastic leukemia.